PENGARUH PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN, SKALA PERUSAHAAN DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR DI BEI PERIODE 2010-2013 (Students' Journal of Economic and Management, 2015)
This study examines the effect of receivables turnover, inventory turnover, and liquidity scale company to profitability.This research was conducted in the Indonesia Stock Exchange using analysis unit manufacturing companies that have gone public. The method used in this research is descriptive quantitative method. Sample using purposive sampling techniques with the study period of 2010 to 2013. The results showed that the turnover of receivables and inventory turnover does not affect the profitability. While the company's scale and liquidity positive and significant impact on profitability. Keywords : Accounts Receivable Turnover, Inventory Turnover, Scale Company, Liquidity andProfitability.